Exploring Jewish literature of the second temple period : A guide for new testament students - Helyer, Larry R. (Downers Grove, Illinois : IVP Academic, 2002)
From the crisis of the Babylonian exile to the rise of rabbinic Judaism -- a span of over six hundred years -- the Jewish people produced a wealth of literature that lies outside the Hebrew Bible. Today it goes under names such as apocrypha and pseudepigrapha, Josephus and Philo, apocalyptic literature and the Dead Sea Scrolls, Mishnah and targums. But line by line, scroll by scroll, it represents the history and theology, the hopes and prayers of a living and diverse Judaism. It is an engrossing subject in and of itself, but for students of the New Testament it offers an invaluable context for understanding the words and actions of Jesus as well as the conversion and thinking of Paul. Exploring Jewish Literature of the Second Temple Period is an introduction to this literature and places it within its historical context. Riding the explosive growth of knowledge of this period, Larry R. Helyer guides students to the heart of the matter. What were the pressures and realities, the questions and dreams that nurtured and provoked these written expressions? And how does this literature throw light on the text of the New Testament and origins of Christianity? - Publisher.
The rise of the Second Commonwealth -- Tales from the Diaspora -- Hellenism invades the Middle East -- Apocalypticism : hope for hard times -- Resistance literature -- The Dead Sea Scrolls : the new-covenant community -- The Dead Sea Scrolls : Scripture & the end times -- "Down in Egypt land" -- Philo Judaeus -- Flavius Josephus : the house that Herod built -- Coping with calamity -- The reconstruction of Judaism -- The world of Mishnah -- The partings of the ways.
Includes bibliographical references and indexes.
Keywords: Bible O.T. -- Apocrypha -- Criticism, interpretation, etc; Apocryphal books -- Criticism, interpretation, etc; Dead Sea scrolls -- Criticism, interpretation, etc; Greek literature -- Jewish authors -- History and criticism; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Bible N.T. -- Criticism, interpretation, etc